Analisis Pengaruh Struktur Modal, Struktur Kepemilikan, dan Karakteristik Perusahaan berpengaruh pada Nilai Perusahaan dengan Kinerja Keuangan dan Manajemen Laba sebagai Variabel Intervening pada Perusahaan Manufaktur Sub Sektor Semen Periode 2019-2023 - Della Widyasari; Hwihanus Hwihanus (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
Firm value is an overall measure of the economic value of a company that includes asset value, profit-making ability, and future growth potential. This study aims to analyze the effect of capital structure, ownership structure, and company characteristics on firm value with financial performance and earnings management as intervening variables in cement sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The research method used is a quantitative method with a secondary data analysis approach obtained from the company's financial statements and annual reports. The results showed that capital structure has a significant negative effect on earnings management and financial performance, but not significant on firm value. Ownership structure is not significant to all variables. Firm characteristics have a significant positive effect on earnings management and firm value. Earnings management has a significant positive effect on firm value, while financial performance has a positive but insignificant relationship. These findings provide practical implications for company management in designing optimal financial strategies to improve company performance and value, as well as for investors in making investment decisions based on relevant financial indicators.